2003
DOI: 10.1159/000072925
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Metals and Solvents and the Risk of Motor Neuron Disease

Abstract: Previous studies based on recalled occupational histories have implicated metal and solvent exposure in the etiology of motor neuron disease (MND). We have used death certificates held in pension fund archives and linked unbiased historical occupational records to investigate the effects of occupational exposure to metals or solvents on the risk of death from MND in 22 cases and 206 controls from 22,526 past employees of a major UK engineering company. We found no evidence of increased risk of death from MND i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
0
18
1
Order By: Relevance
“…These occupations might be related to excessive physical activity and exposure to toxic substances 23,24 . Regarding pesticides, significant increased risk estimates were reported in two studies 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These occupations might be related to excessive physical activity and exposure to toxic substances 23,24 . Regarding pesticides, significant increased risk estimates were reported in two studies 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pesticides, significant increased risk estimates were reported in two studies 25,26 . sALS risk was associated to the exposure to cleaning solvents or degreasers, alcohols or ketones, insecticides, fertilizers, selenium, as well as for occupations potentially exposed to solvents or pesticides (farm-related occupations) 24,27 . To assess the potential value of these findings, they should be replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1970s, most studies have reported an association between exposure to metals, such as lead, mercury or others, and risk of ALS [10,11,12,13,14,15,16,17], although others have failed to find a statistically significantly increased risk of disease [18,19]. The relationship between exposure to pesticides, agricultural occupations and residing in a rural area and risk of ALS has been inconsistent as only about half of the epidemiologic studies, including two meta-analyses, have found an association [14,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The toxic agents most frequently reported, as potentially responsible, are metals (particularly lead, mercury and selenium) [14,15,16,17], solvents [18,19], pesticides [20,21,22,23,24,25] and electric shocks [26,27,28].…”
Section: Introductionmentioning
confidence: 99%